Підвищення ефективності роботи системи пилоприготування котла ТП-92 - Брикайло, Р.; Брикайло, І. (Видавництво Національного університету «Львівська політехніка», 2003)
The ukrainian coal-fired power plants are not enough effective becaus of their worn-out equipment and they fire poor quality coal. Modernization and reconstruction of power plants can increase their effectiveness.